DINAMIKA KONFLIK AKTOR DALAM PEREBUTAN JABATAN KETUA DPD II PARTAI GOLKAR (GOLONGAN KARYA) DI KABUPATEN ROKAN HULU TAHUN 2017 - Ade Permana; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This is the party Golkar that as long history in Indonesia where shortly earlier named the Secretariat With Golongan Karya and this party that do this is the party ruler when the New Order. A long journey the party Golkar never be prevented from dynamics internal conflicts, in Rokan Hulu regency, internal conflicts happened in DPD II Golkar Rokan Hulu regency, where the conflict began since the establishment of the head of the Golkar Rokan Hulu namely Suparman by the corruption eradication commission (KPK) on 7 June 2016 on suspicion of embezzlement the draft (RAPBD) of riau year 2014-2015, the party Golkar management command a vacuum in the position of the head DPD II Golkar Rokan Hulu because Suparman being held by the KPK, and remember office Suparman also has been completed in early of the year 2017. To fill vacancy of the head the party Golkar Rokan Hulu, and it is Musda in different times and places on 8 January 2017 and 7 February 2017, the race position will not could be avoided between Sari Antoni and Nono Patria Pratama, because the position of the head Golkar in Rokan Hulu regencyis very strategic, the party is the winner second in Pileg 2014 and winners of the election Pilkada in Rokan Hulu regency of the year 2015.The formulation of a problem in this research was “How of the dynamics of conflict in DPD II Golkar Rokan Hulu regency of the year 2017”. The purpose of this research is to find the dynamics of conflict for Golongan Karya (GOLKAR) 2017 in DPD II Golkar Rokan Hulu regency of Riau.This research result indicates that conflict in internal the party Golkar Rokan Hulu is because the race as the head of DPD II the party Golkar Rokan Hulu between Sari Antoni and Nono Patria Pratama, because the position of the head Golkar in Rokan Hulu strategic. This conflict are part conflict the surface and conflict resolution by means of Non Zero Sum Game.Keyword: The party Golkar, Dynamics of Conflict